Factors Affecting the Sustainability of Micro Enterprises Dodol Snack Centers Bengkel Market and Its Relationship to the Islamic Economic Perspective - Ahmad Fauzi; Yusrizal Yusrizal; Juliana Nasution (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
It can be seen that MSMEs are one of the sectors of economic activity that survive and have sustainability. One area that has MSMEs that still survive today is North Sumatra, specifically Pasar Bengkel Village, Perbaungan District, Serdang Bedagai Regency. Pasar Bengkel Village is a favorite place for residents and travelers who like local snacks or culinary specialties. However, now the Dodol MSME culinary center will be a distant memory due to declining demand and purchasing power. Also, Dodol micro business actors in the Bengkel Village area have complained about the reduction in the sales value of their Dodol products since the operation of the Medan-Tebing Tinggi toll road. The reason is that many transport passengers and car drivers don’t have time to stop because they are crossing the toll lane. This makes consumers or buyers reluctant to stop by this Bengkel market, resulting in low turnover, resulting in dozens of stalls being closed. This research aims to determine the influence of product innovation, product sales methods, information technology, market share, ethics of honesty and transparency, and halal products on the sustainability of the micro business Dodol Snack Center Pasar Bengkel simultaneously. This research uses a quantitative research approach with multiple regression methods. The number of samples in this research was 68 MSME entrepreneurs of Pasar Bengkel Dodol Snacks. This research shows that there is a significant influence of product innovation, market share, and product halalness on the sustainability of the Pasar Bengkel Dodol Snack Center micro-enterprise.